Construção de uma proposta de formação continuada para professores de classe hospitalar - Mazer-Gonçalves, Sheila Maria (2013)
This qualitative study of phenomenological basis, involves continuing education for teachers of Class Hospital. Aims to build, implement and evaluate, with the teacher 's Hospital Class, a proposal for continuing education to reframe the teaching practice in the educational space. Two teachers participated in a press conference audio-recorded with the core issues, which promoted the description of their practice in Hospital Class, signaling that knowledge could enhance the performance. The interview was transcribed and passed to the data analysis according to the methodology of phenomenological investigation. In a second stage of the research, we implemented a continuing education program for teachers Class Hospital. Monthly meetings were marked with two hours, in a Municipal Hospital in São Paulo. The meetings were described in a field notebook for further discussion of the data. Finally, by means of a written questionnaire, the teachers made the bid evaluation and the contribution of continuing education in pedagogical practice in Hospital Class. It can be considered that the interview was the initial prime importance to understand the knowledge and practices that teachers have in their Class Hospital pedagogical work at the hospital. Thus, it was possible to seek subsidies to build the proposed intervention, since the teachers themselves pointed out that it would be important to be worked on in-service training. The work of the researcher in organizing training meetings, within Class Hospital where they operate, from texts, videos and dynamic content which concerned the themes selected by the teachers can be considered a suitable design to think about ongoing education. At the end of the training process, it was revealed that the teachers were able to reframe the actions and pedagogical practices of the Hospital Class , reflecting on past experiences and imposing changes in teaching strategies and learning with students , patients and promoting actions with caregivers and staff health . Thus, it is relevant to note that the Continuing Education Program in service was built from the demands presented at each meeting by the teachers themselves and the application of the proposed training was also possible for the effort in giving them space, time and willingness to self-assess and then print new meanings to the practice teaching experience in Hospital Class. The teachers showed the importance of ongoing education as a space to reflect on practice and experiences and restructure work, advancing knowledge and enriching educational activities.